2022
DOI: 10.1111/soru.12390
|View full text |Cite
|
Sign up to set email alerts
|

The virtual good farmer: Farmers’ use of social media and the (re)presentation of “good farming”

Abstract: This paper advances the literature on the ‘good farmer’ by considering the role social media may play in the presentation, refinement and reworking of notions of good farming. In exploring these ideas, the paper brings current understandings of the good farmer into conversation with those literatures on online capital exchange and the extensions of Goffman's ideas of identity performance. The paper draws on analysis of 5,000 farming tweets and interviews with 22 farmers who utilize Twitter. The paper considers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 38 publications
(86 reference statements)
1
3
0
1
Order By: Relevance
“…Overall, discussed findings within four main aspects are in line with the polymedia-new theory of digital media (Madianou and Miller 2018) and social identity studies on farmers in the digital age (Newsome 2021;Ogunyiola and Gardezi 2022;Riley and Robertson 2022). All these studies suggest that the use of new media is not just changing in technology levels but also changes in behaviors and relationships, resulting in emotional, social, and moral consequences.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…Overall, discussed findings within four main aspects are in line with the polymedia-new theory of digital media (Madianou and Miller 2018) and social identity studies on farmers in the digital age (Newsome 2021;Ogunyiola and Gardezi 2022;Riley and Robertson 2022). All these studies suggest that the use of new media is not just changing in technology levels but also changes in behaviors and relationships, resulting in emotional, social, and moral consequences.…”
Section: Discussionsupporting
confidence: 76%
“…The agrarian literature on the new media use of farmers has suggested that new media use might redefine farming identities via emotional support via stronger online connections (Sergi and Bonneau 2016). For example, participatory media may let farmers' social media posts resonate with "empathy rituals" when discussing about the difficulties of farming practices (Brownlie and Shaw 2019;Riley and Robertson 2021). The findings in this study increase knowledge about the emotional consequences of "The New World of Work" by studying the subjective emotions of young farmers.…”
Section: Emotional Consequencesmentioning
confidence: 72%
See 2 more Smart Citations
“…文件"提出"实施数字乡村战略"以来,国家及其各部委陆续发布一系列数字乡村发展规 划、行动指南与试点名单,期望通过数字技术发展实现城乡融合与共同富裕 [1] 。数字乡村 建设在整合乡村生产要素、延长乡村产业链、促进产业融合发展方面发挥着重要作用 [2,3] , 数字技术推动着农业发展的精细化、智能化和信息化 [4] ,不仅调整了乡村自然资源的利用 方式,也为农业资源与其他类型资源的融合发展提供新的路径 [5] 。 数字技术的嵌入使得乡村资源的开发、利用和整合也呈现出新的方式。第一,数字 技术将过去依赖于地方性经验、血缘与地缘关系的资源利用方式转变为以算法为核心的 智能化和精准化的利用方式,这尤其体现在智慧农业的发展上。比如人工智能技术打造 农业的集约管理系统,使得农作物能够精准地在特定的时间点得到播种、灌溉和收获 [6] ; 大数据技术通过搜集当地的自然灾害数据为农业灾害的发生提供预测服务 [7] 等;数字技术 还推动农业生产过程的透明化,比如区块链技术能够通过"去中心化"的治理思维实现 农产品的生产过程追踪和质量监测,打通生产与消费之间的隔阂 [8] 。第二,数字技术发展 重构了乡村资本、土地和劳动力资源的流动方向和速度,城市化发展引起的城乡二元结 构促使乡村劳动力向城市集聚。城市化的发展使得乡村"空心化"日益严重 [9] ,而数字技 术发展改变了城乡互动的方式,也使得资源流动方向发生转变 [10] 。比如电商产业向地价 38 卷 自 然 资 源 学 报 更低廉的乡村地带转移,形成"淘宝村"现象,促进乡村土地资源的盘活 [11] ,平台经济 重构着劳动力流动的方向,乡村居民能够通过数字平台获得线上的就业机会,从而减少 了向城市流动的劳动力资源 [12] ,乡村数字基础设施建设牵动资本从城市流向乡村 [13] 等。 第三,数字媒体的发展推动着乡村社会文化资源的重塑与活化。在乡村内部数字媒体成 为村民之间沟通的工具,也进一步加强了村民之间的联系和乡村社区凝聚力 [14] ,在乡村 外部其地方形象和文化资源能够通过数字媒体得以广泛地传播,重塑着受众对乡村的认 知和想象 [15] ,乡村形象在媒体的重新表征进一步吸引城市居民关注乡村,带动乡村旅游 发展 [16] 。 乡村资源开发利用的转型是乡村地域人地关系转变的体现,数字技术转变乡村资源 开发利用方式的同时,也在推动乡村空间的重构。当前国内外关于乡村空间重构与数字 技术研究主要聚焦于宏观层面的探讨,比如通过建立乡村数字化测度指标体系分析数字 乡村的空间特征 [17] ,从政策的顶层设计分析数字技术对农业空间的重构 [18] ,基于 GIS 技术 测算乡村数字化与土地利用关系 [19] 等,当前研究更多将乡村看作是物质的、生产的空 间,而忽视了乡村空间的社会特征,而当前人文地理学的"数字转向"有助于为数字乡 村建设提供新的研究视角,特别是从社会文化的视角探讨数字技术为乡村发展带来的空 间效应。数字地理学认为数字技术不只是附庸于人的工具,而是改变当代城乡空间发展 的"行动者" [20] ,数字信息的生产、流通和储存的过程中都与社会发展发生着各种联 系,继而重塑着人们对世界的认识与实践 [21] 。比如数字技术发展引起"时空压缩"的效 应 [22] 、建构出虚构的"赛博空间" [23] 、数字平台和互联网成为要素流动新的方式等 [24] ,都 表明数字技术正在深刻地重构地理环境中的人地关系、空间关系和社会关系。 在数字技术支持下,乡村资源的开发、利用和整合重构传统的乡村空间,推动着乡 村地域系统的转型 (图 1) 。数字技术发展使得乡村资源的利用发生在实体和虚拟两个场 域。在实体场域中,数字驱动下的"时空压缩"效应推动了乡村与外部空间的要素流 动,为乡村资源的开发利用提供新的动力 [25] ,在算法、平台和智能技术的支持下农业生 产的时间性和空间性得以改变,进而重塑乡村资源利用、流动的速度 [26] ;在虚拟场域 中,数字技术为农业生产提供了虚拟空间的支持,在互联网、区块链和数字平台等支持 下,农产品的生产、运输和销售不再局限于实体空间,而是在数字与实体相混合的空间中 实现,这也使得更多元的主体参与到农业生产之中,同时推动着乡村生产关系的转变 [27] ; 图 1 数字技术支撑下的乡村空间 村话语,创造出乡村媒介形象 [28] ,既改变了乡村居民对外部世界的认知 [29] ,又改变了外 部城市居民对乡村空间的想象。 农旅资源的整合是乡村产业融合的重要基础 [30,31]…”
unclassified